Prevalence of coronary risk factors in a sample of Chinese women in Kuala Lumpur - Khor, Geok Lin; Hsu-Hage, Bridget Huey-Huey; Sundram, K.; Wahlqvist, Mark L. (Malaysian Medical Association, 1997)
Several risk factors for cardiovascular disease amongst a sample of urban Chinese women were investigated. These factors included body mass index (BMI), waist hip ratio, total blood cholesterol (TC), HDL-cholesterol and Lp(a) levels, blood pressure, cigarette smoking, family history of chronic disease, dietary habits and frequency of selected food intake. The subjects were found to have coronary risks with respect to BMI and TC level, both of which increased with age of the women. Hypertension, HDL-cholesterol and Lp(a) levels appeared not to pose as risk factors amongst these subjects. Dietary habits and intake showed significant correlations with subjects' BMI status. Health promotion is called for towards reducing the modifiable coronary risk factors.